The effect of active learning on academic performance in a Norwegian primary school setting–the Health Oriented Pedagogical Project (HOPP) - Fredriksen, Per Morten; Bjerva, Trine; Mamen, Asgeir (Frontiers in Education, 2025)
BackgroundNumerous systematic reviews, with varying degrees of certainty, have suggested a beneficial link between physical activity and academic achievement.MethodsThe Health Oriented Pedagogical Project (HOPP) in Horten, Norway, integrates active learning in seven elementary schools’ curricula (n = 1,545), aiming to merge physical activity with academic instruction. The control group consisted of two schools from Akershus County, doing standard teaching (n = 752). The data were collected from 2015 to 2019.ResultsThe results highlight the active learning potential to complement traditional teaching methods and foster overall academic success in elementary education. Active learning, partially replacing traditional classroom methods with physical tasks, yielded significant academic benefits. Secular trends for national tests in 5th-grade intervention school students across five years showed improvement compared to control schools in English, arithmetic, and reading. Both intervention and control schools displayed a significant change in slope across the study period. Compared to national median results, the intervention schools also revealed an improvement.ConclusionHOPP’s findings underscore the effectiveness of active learning in enhancing academic performance, with intervention schools surpassing national medians after four years of intervention.